Differential Peripheral Blood Gene Expression Profile Based on Her2 Expression on Primary Tumors of Breast Cancer Patients - Tudoran, Oana (Public Library of Science, 2014)
Breast cancer prognosis and treatment is highly dependent on the molecular features of the primary tumors. These tumors release specific molecules into the environment that trigger characteristic responses into the circulatory cells. In this study we investigated the expression pattern of 84 genes known to be involved in breast cancer signaling in the peripheral blood of breast cancer patients with ER-, PR- primary tumors. The patients were grouped according to Her2 expression on the primary tumors in Her2+ and Her2- cohorts. Transcriptional analysis revealed 15 genes to be differentially expressed between the two groups highlighting that Her2 signaling in primary tumors could be associated with specific blood gene expression. We found CCNA1 to be up-regulated, while ERBB2, RASSF1, CDH1, MKI67, GATA3, GLI1, SFN, PTGS2, JUN, NOTCH1, CTNNB1, KRT8, SRC, and HIC1 genes were down-regulated in the blood of triple negative breast cancer patients compared to Her2+ cohort. IPA network analysis predicts that the identified genes are interconnected and regulate each other. These genes code for cell cycle regulators, cell adhesion molecules, transcription factors or signal transducers that modulate immune signaling, several genes being also associated with cancer progression and treatment response. These results indicate an altered immune signaling in the peripheral blood of triple negative breast cancer patients. The involvement of the immune system is necessary in favorable treatment response, therefore these results could explain the low response rates observed for triple negative breast cancer patients.